Ethnomathematics exploration in the Mappacci tradition of the Bugis ethnic group - Ahmad, Asdar; Naufal, Muhammad Ammar; Arwadi, Fajar; Jeranah, Jeranah (Universitas Papua, 2024)
The incorporation of cultural elements into mathematics education has the potential to enhance learning outcomes. This investigation sought to identify and elucidate the mathematical concepts inherent in the Mappacci tradition of Bugis culture. Employing qualitative ethnography, the study discerned mathematical patterns within the ritualistic practices through a combination of observations, interviews, documentation, and literature review. Analysis of the gathered data involved qualitative methodologies including domain analysis, taxonomy analysis, componential analysis, and analysis of cultural themes. Findings revealed that the use of specific odd and even numbers, such as 1, 7, and 9, alongside those prominent in the Pacci presentation, conveys fundamental life principles such as perfection and integrity. Moreover, geometric forms like triangles and rectangles symbolize stability and essential virtues, reflecting the cyclical essence of life and providing spiritual guidance. The symbolic application of Inai (Pacci) leaves underscore’s themes of unity and purification, reinforcing familial bonds. Furthermore, the adherence to numerical values like 30 and 3 in rituals reflects the influence of Islamic teachings, emphasizing the significance of triadic patterns in fostering religious and social cohesion. These cultural elements imbue both community and individual existence with profound ethical, spiritual, and cultural values, thereby enriching societal fabric.